2012
DOI: 10.1007/s11481-012-9360-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Viral and Anti-Inflammatory Mechanisms of the Innate Immune Transcription Factor Interferon Regulatory Factor 3: Relevance to Human CNS Diseases

Abstract: Interferon regulatory factor 3 (IRF3) is a transcription factor critical in the induction of antiviral immunity. IRF3 is activated following stimulation of cell membrane or cytosolic nucleic acid sensors and is essential in the induction of the IFNβ gene. Most cells constitutively express IRF3 in vitro, but little is known about the regulation of expression of IRF3 in vivo. Immunohistochemical analysis of selected human and mouse tissues demonstrated that IRF3 expression is highly organ- and cell-type specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 80 publications
0
25
0
Order By: Relevance
“…CXCL11 was chosen as a marker of successful delivery because it has been reported to be prominently induced by IFNβ48. IRF3 is a key transcriptional regulator of the IFNα and β genes, as well as a direct activator of many IFN-stimulated genes involved in establishing an antiviral state49. CCL4 played a crucial role in protection by IFNβ against gp120 neurotoxicity in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…CXCL11 was chosen as a marker of successful delivery because it has been reported to be prominently induced by IFNβ48. IRF3 is a key transcriptional regulator of the IFNα and β genes, as well as a direct activator of many IFN-stimulated genes involved in establishing an antiviral state49. CCL4 played a crucial role in protection by IFNβ against gp120 neurotoxicity in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…We and others showed that TNF-α and subsequent NF-κB activation lead to increased proliferation of SVZ NSCs [85][86][87][88] without affecting their neuronal and glial differentiation. Contrarily to NF-κB, in the central nervous system IRF3 is believed to play a mainly antiinflammatory role (reviewed in [89]). In NSCs cultures, IRF3-target gene IFN-β inhibits the proliferation [90].…”
Section: Neural Stem Cells / Neuronal Progenitor Cellsmentioning
confidence: 99%
“…Tarassishin et al (41) recently demonstrated that MNGCs in the brain that were highly associated with IRF3 induction. Another group, Hornik et al (42) demonstrated in a microglia cell line that multinucleation could be triggered by TLR ligands, IFNβ, and proteins associated with Parkinson’s disease alpha-synuclein) and Alzheimer’s disease ((amyloid-beta).…”
Section: Innate Immunity In the Context Of Hiv Associated Neurologicamentioning
confidence: 99%